2017
DOI: 10.12816/0041704
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Management of Venous Thromboembolic Diseases in Donor of Living Donor Liver Transplant

Abstract: Background: liver transplantation surgically replaces a failing or diseased liver with one that is normal and healthy. At this time, transplantation is the only cure for liver insufficiency or liver failure because no device or machine reliably performs all of the functions of the liver. Aim of the Work: this study aimed to highlight risk factors of the venous thromboembolism in donors of living donor liver transplant and its management. Patients and Methods: this study included 40 patients who underwent hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Bahaa El Din et al [ 17 ] completed a small review of 40 patients who underwent liver transplantation and found while ACAs did not provide significant evidence of producing venous thrombosis, LAs were a statistically significant indicator of venous thrombosis. Furmańczyk-Zawiska et al [ 18 ] completed a similar study determining whether the presence of APL would predict thrombotic risk and determined that the variable nature of ACAs make them an unreliable predictor of thrombotic events. Furmańczyk-Zawiska et al concluded that monitoring patients with APL is not necessary in liver transplant patient.…”
Section: Discussionmentioning
confidence: 99%
“…Bahaa El Din et al [ 17 ] completed a small review of 40 patients who underwent liver transplantation and found while ACAs did not provide significant evidence of producing venous thrombosis, LAs were a statistically significant indicator of venous thrombosis. Furmańczyk-Zawiska et al [ 18 ] completed a similar study determining whether the presence of APL would predict thrombotic risk and determined that the variable nature of ACAs make them an unreliable predictor of thrombotic events. Furmańczyk-Zawiska et al concluded that monitoring patients with APL is not necessary in liver transplant patient.…”
Section: Discussionmentioning
confidence: 99%